On the Rayleigh Quotient for Singular Values (Journal of Computational Mathematics, 2007)
In this paper, the theoretical analysis for the Rayleigh quotient matrix is studied, and some results of the Rayleigh quotient (matrix) of Hermitian matrices are extended to those for arbitrary matrix on one hand. On the other hand, some unitarily invariant norm bounds for singular values are presented for Rayleigh quotient matrices. Our results improve the existing bounds.